Exploring the motivational pathways to subjective well-being in urban forest parks of Fuzhou, China: a structural equation modelling analysis - Lu, Jing; Maruthaveeran, Sreetheran; Shahidan, Mohd Fairuz; Liu, Qunyue (Multidisciplinary Digital Publishing Institute, 2025)
Understanding visitors’ motivations is essential for enhancing the perceived well-being of urban residents and promoting overall human welfare. Grounded in an integrated framework combining Self-Determination Theory and the Theory of Planned Behaviour, this study investigates how different types of motivation, i.e., amotivation, extrinsic motivation, and intrinsic motivation, influence visitors’ subjective well-being through the mediating role of behavioral intention. The theoretical model was tested using primary data collected via structured questionnaires from three urban forest parks in Fuzhou, China. Exploratory factor analysis identified latent constructs, and confirmatory factor analysis validated the measurement model. Structural Equation Modeling (SEM) was employed to test the proposed hypotheses. The results reveal that intrinsic motivation significantly enhances behavioral intention, whereas extrinsic motivation and amotivation have a negative association. Behavioral intention has a strong and positive influence on subjective well-being. Both intrinsic and extrinsic motivations indirectly affect well-being through the complete mediation of behavioral intention. In contrast, amotivation follows a dual pathway: it negatively influences well-being through partial mediation and also exerts a direct positive association. These findings underscore the central mediating role of behavioral intention in connecting motivation and well-being outcomes in urban forest park visitation. The study highlights the importance for policymakers and managers of considering how different forms of motivation affect the attainment of subjective well-being, and of incorporating these factors into future decisions concerning urban forest park so as to facilitate comparable findings and support further generalizations.